2013
DOI: 10.1089/ars.2012.5104
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Energy and Redox Signaling in Plants

Abstract: Significance: For a plant to grow and develop, energy and appropriate building blocks are a fundamental requirement. Mitochondrial respiration is a vital source for both. The delicate redox processes that make up respiration are affected by the plant's changing environment. Therefore, mitochondrial regulation is critically important to maintain cellular homeostasis. This involves sensing signals from changes in mitochondrial physiology, transducing this information, and mounting tailored responses, by either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 252 publications
(229 reference statements)
0
113
0
Order By: Relevance
“…In particular, exemplary studies have emphasized the importance of salicylic acid-triggered mitochondrial ROS production (Gleason et al, 2011), controlled mitochondrial protein import (Huang et al, 2013), and mitochondrial retrograde signaling control (Vellosillo et al, 2013) in defense against microbial pathogens. These finding are supported by recent Arabidopsis transcriptome meta-analyses suggesting that upregulation of defense gene expression might be under mitochondrial retrograde control (Schwarzländer et al, 2012) and that transcripts of alternative respiration, representing marker genes for retrograde signaling, are specifically induced by Bgh attack (Schwarzländer and Finkemeier, 2013). Consequently, it is not surprising that microbial pathogens evolved effector molecules that target mitochondria in order to manipulate their functionality (Block et al, 2010).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In particular, exemplary studies have emphasized the importance of salicylic acid-triggered mitochondrial ROS production (Gleason et al, 2011), controlled mitochondrial protein import (Huang et al, 2013), and mitochondrial retrograde signaling control (Vellosillo et al, 2013) in defense against microbial pathogens. These finding are supported by recent Arabidopsis transcriptome meta-analyses suggesting that upregulation of defense gene expression might be under mitochondrial retrograde control (Schwarzländer et al, 2012) and that transcripts of alternative respiration, representing marker genes for retrograde signaling, are specifically induced by Bgh attack (Schwarzländer and Finkemeier, 2013). Consequently, it is not surprising that microbial pathogens evolved effector molecules that target mitochondria in order to manipulate their functionality (Block et al, 2010).…”
Section: Discussionmentioning
confidence: 74%
“…Using Arabidopsis lines expressing the mitochondrial redox sensor mtroGFP2, we were able to show here that mitochondria immobilized at plant-microbe interaction sites exhibit a redox shift toward oxidation as a likely consequence of localized generation of ROS. Regardless of whether mitochondria are the prime source of ROS, or a target for oxidative damage, or whether perturbation of mitochondrial function and dynamics is the cause or consequence of the observed elevated oxidation status, it is important to note that mitochondrial ROS can trigger retrograde signaling and hypersensitive cell death in plants (Schwarzländer and Finkemeier, 2013;Ng et al, 2014). Thus, it is tempting to speculate that the original evolutionary function of the mitochondrial subpopulation observed in this study was to contribute to pathogen-induced retrograde signaling to the nucleus and transcriptional reprogramming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perturbation of mitochondrial function often leads to an oxidative inhibition of the mitochondrial aconitase, which is followed by a rise in cellular citrate levels (Vanlerberghe and McIntosh, 1994;Morgan et al, 2008;Lehmann et al, 2009;Gupta et al, 2012). Mitochondrial citrate was discussed as a possible mediator of mitochondrial retrograde signals in plants as well as in yeast cells, but an in-depth transcriptome study was lacking so far (Vanlerberghe and McIntosh, 1994;Mackenzie and McIntosh, 1999;McCammon et al, 2003;Clifton et al, 2005;Schwarzländer and Finkemeier, 2013). Vanlerberghe and McIntosh (1996) already reported that the AOX1 transcript level responded to increased levels of citrate that were supplied externally or were increased internally through the inhibition of aconitase using monofluroacetate.…”
Section: Citrate and Malate Have Unique Roles In Cellular Metabolismmentioning
confidence: 99%
“…In addition to their damaging effects, mtROS probably act as MRR-triggering signaling molecules (Vanlerberghe et al, 2002;Rhoads et al, 2006). Calcium originating from the mitochondria might also be an MRR signal (Subbaiah et al, 1998), as seen in mammalian cells (Butow and Avadhani, 2004), as well as changes in mitochondrial redox status and metabolites (Schwarzländer and Finkemeier, 2013).…”
Section: Introductionmentioning
confidence: 99%